Why I sneeze, shiver, hiccup, and yawn - Berger, Melvin; Meisel, Paul; Berger, Melvin (New York, N.Y. : HarperCollinsPublishers, 2000)
An introduction to reflex acts that explains why we sneeze, shiver, hiccup, and yawn.
Rev. ed. of: Why I cough, sneeze, shiver, hiccup, & yawn. New York : Crowell, c1983.
480
Accelerated Reader AR
Keywords: Reflexes -- Juvenile literature; Reflexes